Effect of inorganic salts on bacterial omega-3 PUFA production. Issue 3 (16th March 2017) - Abd Elrazak, Ahmed; Ward, Alan C.; Glassey, Jarka
ABSTRACT: The increasing demand of omega-3 in the market and the challenges facing its conventional supplies led to an increasing interest to microbial omega-3 sources. This research concentrates on the statistical role of some metal ions on the biosynthesis and productivity of eicosapentaenoic acid (essential omega-3 element) in bacterial isolate, Shewanella 717. A Plackett–Burman design was applied to screen the main effect of all metal salts entrenched in the artificial sea water medium components. Four salts, in particular, in addition to the interaction among them were highlighted as having a statistically significant effect upon the growth and/or eicosapentaenoic acid production. A subsequent central composite design was performed to determine the exact optimum concentration of each of the chosen variables which was found to be 2.5, 1.8, 1.2, and 23 g/l, for Na2 HPO4, MgSO4, KCl, and NaCl, respectively. All the experiments were performed with the minimal amount of carbon and nitrogen to eliminate any potential masking effect. A bioreactor batch run was operated and the ion uptake was monitored, using EDAX® electron microscopy, concluding that the process of microbial omega-3 production could be a phosphate-limited process. Optimizing the concentration of the tested metal ions led to a remarkable increase in the omega-3 productivity resulted in a 30, 9, and 10 times increase in yield, concentration, and percentage to the total fatty acids, respectively, even though the carbon and nitrogen were kept constant all over the research work.